2016
DOI: 10.1292/jvms.15-0486
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous oral chytridiomycosis in wild bullfrog tadpoles in Japan

Abstract: Batrachochytrium dendrobatidis (Bd) infects Anuran larvae (tadpole) mouthparts and causes oral chytridiomycosis, which can be diagnosed in tadpoles by detecting mouthparts deformities. However, oral chytridiomycosis may or may not be observable, depending on species, tadpole stage and season, and has never been reported in Japan. We aimed to observe oral chytridiomycosis characteristics in bullfrog (Lithobates catesbeiana) tadpoles, determine associated pathologic features and investigate the usability of bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
7
2
1
Order By: Relevance
“…We previously confirmed that the wild bullfrog Lithobates catesbeiana tadpole is a suitable animal model for investigating Bd distribution in Japan [ 5 ]. Thus, in the present study, we compared the sensitivity of two detection methods for Bd: nested polymerase chain reaction (PCR) for Bd genomic DNA from (1) swab-scraped mouthpart samples (hereon referred to as “swab nested PCR”) and (2) resected mouthpart samples (hereon referred to as “tissue nested PCR”).…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…We previously confirmed that the wild bullfrog Lithobates catesbeiana tadpole is a suitable animal model for investigating Bd distribution in Japan [ 5 ]. Thus, in the present study, we compared the sensitivity of two detection methods for Bd: nested polymerase chain reaction (PCR) for Bd genomic DNA from (1) swab-scraped mouthpart samples (hereon referred to as “swab nested PCR”) and (2) resected mouthpart samples (hereon referred to as “tissue nested PCR”).…”
mentioning
confidence: 78%
“…The detection rates of swab nested PCR and tissue nested PCR were investigated using samples from 120 wild bullfrog tadpoles. The tadpoles were collected from two sites: 60 from Saihaku county in Tottori prefecture on May 13, 2012, and 60 from Seihi town, Saikai city of Nagasaki prefecture on February 17, 2013; these collection times corresponded to the time at which the Bd infection rate is reportedly high [ 5 , 10 ], in conformity with the Invasive Alien Species Act [ 7 ]. The collected bullfrog tadpoles were anesthetized and then euthanized, as described previously [ 5 ], for measuring body length and body weight.…”
mentioning
confidence: 99%
See 3 more Smart Citations